ANALYSIS OF FACTORS THAT AFFECT TAX COMPLIANCE OF HOTEL ENTREPRENEURS IN PAYING TAXES - Galih Prasetiyo; Erwin Saraswati (Jurnal Ilmiah Mahasiswa FEB, 2012)
The objective of this research is to analyze what kind of factors that affect tax compliance of hotel entrepreneurs in Batu City. The method used is survey research method by using questioners as the research instrument. The respondents are all  of the hotel entrepreneurs in Batu City. Analysis used in this research is the multiple linear regression analysis. The result of this analyses state that there are some variables which give positive and significant influence towards the tax compliance, those are: tax audit, tax sanction, tax perception, and tax payers awareness variables. While the variables of tax laws, tax education, finance condition, and the system of government and law are not the factors that determine the tax compliance. Key words:  tax compliance of hotel entrepreneurs, tax audit, tax sanction, tax perception, tax payers awareness, tax laws, tax education, finance condition, the system of government and law.